Botanic Garden Tourism: An Implementation of Sustainability Principle through Tourism Private Partner Collaboration in Bogor Botanic Garden - Maranisya, Ulfi; Muntasib, E.K.S Harini; Soekmad, Rinekso; Hermawan, Rachmad (Centre For Tourism Planning and Development, 2025)
All tourism activities in the botanic garden should support its primary function. Tourism activities in botanic gardens are required to maintain the sustainability of botanic gardens as plant ex-situ conservation. Since 2021, the private sector has managed tourism in the Bogor Botanic Garden. The importance of evaluating the sustainability of ecological/environmental, socio-cultural, and institutional aspects in the Bogor Botanic Garden after private partners manage the tourism. The research method uses Multidimensional scaling RAP-Sustourism. The research informants include the private sector, the government, and academia. The ecological/environmental dimension, with a score of 75.25%, is in good or very sustainable status. The socio-cultural dimension, with a score of 56.40%, has a reasonably sustainable status. The institutional dimension with a score of 48.69%, is less sustainable. The tourism personnel training program and sustainable tourism rules should be available at the Bogor Botanic Garden. This can control the tourism concept developed in the Bogor Botanic Garden. The Bogor Botanic Garden needs tourism human resources who understand botanic gardens and their plant collections.